Tax evasion through fraudulent financial reporting amongst SMEs in Malaysia. Issue 1 (12th August 2020) - Ngah, Zainal Abidin; Ismail, Norashikin; Abd Hamid, Nadiah
Abstract : Purpose: The purpose of this paper is to tackle one of the issues in tax evasion, that is from the perspective of fraudulent financial reporting amongst small and medium-sized enterprises (SMEs) in Malaysia. This study is intended to examine the relationships between certain company attributes, namely, company ownership structure, the size of company and the frequency of tax audits and how they relate to tax evasion practices amongst SMEs in Malaysia. Design/methodology/approach: This paper examined 397 companies which have been audited by the Inland Revenue Board of Malaysia (IRBM) during the years 2016 and 2017. A research model was developed and the authors use ordinary least square regression analysis to examine the effect of three prominent independent variables, which are company ownership structure, the size of company and the frequency of tax audits on SMEs' tax evasion practices in Malaysia. Findings: The authors find that family ownership firms and company size have statistically significant positive relationship with tax evasion practices detected during tax audits. The results also show that the frequency of tax audits conducted positively affect the increase of tax evasion activities amongst SMEs in Malaysia. Originality/value: To the best of the authors' knowledge, this study could be the first in Malaysia that uses the actual audited data examining the fraudulent financial reporting cases amongst SMEs, and this could provide important insights to the IRBM to enable this tax authority to improve its policy-making decisions in relation to selecting the right companies for audits in the future and subsequently may assist its collection department in generating additional income for the nation.